177 Largest Series of Mild-Moderate Motor Vehicle Accident-Associated Thoracolumbar Compression Fractures: Prognosis and Outcome. (1st August 2016) - Soliman, Hesham M.; Nguyen, Ha; Pintar, Frank A.; Yoganandan, Narayan; Kurpad, Shekar N.; Maiman, Dennis J.
Abstract: INTRODUCTION: According to the latest version of the Abbreviated Injury Scale (AIS), all Thoraco-Lumbar Compression Fractures (TLCF) with >20% loss of height, were branded code 3 injuries, reflecting a threat for life or permanent disability. However, clinical observation suggests that that TLCF with <40% loss of height and without neurological deficits, have been noted to have a better clinical prognosis, prompting the need to segregate these injuries differently, revise the classification, and review outcomes. METHODS: Charts and radiographs of patients admitted to our institution with isolated TLCF between 2008 and 2015 were reviewed. We collected data on severity of compression, treatment, and long-term outcomes to determine the threshold of permanent injury. Vertebral bodies at the level of fracture were measured both anteriorly and posteriorly, and compared with adjacent segments; percentage compression was calculated. RESULTS: Records of 1470 patients were reviewed for this effort of traumatic fractures to the thoracic or lumbar spine. Six hundred ninety-five isolated compression fractures were identified, of which 195 were in auto accidents. Ages ranged from 19 to 82, with a male: female ratio of 60:40. No patient with compression of less than 40% underwent surgery unless presenting with a neurological deficit. The only patients undergoing surgical treatment without neurological deficit had compression of 40% or higher; those showed evidence of retropulsion of bone into the spinal canal. Only 1 patient had long-term pain or required long-term treatment for smaller losses in vertebral body height. The use of orthosis in patients with less than 40% compression was of no value in terms of outcomes. Although there were more TLCF in the non-motor vehicle accident population, outcomes were similar. About 35% of the TLCF in the <40% group did not use a brace. The use of orthosis (thoracolumbar spine orthotic device, TLSO) in patients with less than 40% compression was of no value in terms of outcomes, because both the brace and without-brace groups had similar outcomes. CONCLUSION: These results are consistent with evolving clinical thinking, resulting in decreasing surgical incidence and orthosis use.